2009
DOI: 10.1097/rct.0b013e31818474b8
|View full text |Cite
|
Sign up to set email alerts
|

Increased Risk of General Anesthesia for High-Risk Patients Undergoing Magnetic Resonance Imaging

Abstract: Over the last 2 decades, the scope of anesthesia practice has expanded to include remote sites away from the operating room. As the number of diagnostic and therapeutic interventions performed outside the operating room continues to increase, anesthesiologists are being faced with challenges of providing care for more medically complex patients while adapting to fewer resources, with lack of support system commonly available in the operating room. In this article, we present three pediatric cases resulting in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 9 publications
0
29
0
Order By: Relevance
“…In either model, moving an anesthetized patient from one place to another is logistically challenging and increases the risk. The study Greenberg presented attempted to assess this risk and showed 3 deaths in 11,700 anesthetics, a risk of 1 in 3,900 [3]. But the small numerator in this study makes the real risk hard to evaluate and all three patients had co-morbidities, similar to the Melbourne study.…”
Section: Short-term Risks Of Anesthesiamentioning
confidence: 82%
“…In either model, moving an anesthetized patient from one place to another is logistically challenging and increases the risk. The study Greenberg presented attempted to assess this risk and showed 3 deaths in 11,700 anesthetics, a risk of 1 in 3,900 [3]. But the small numerator in this study makes the real risk hard to evaluate and all three patients had co-morbidities, similar to the Melbourne study.…”
Section: Short-term Risks Of Anesthesiamentioning
confidence: 82%
“…The patients weighed less than 7 kg and were considered high anesthetic risk. Their risk of death of 1 in 3,900 was nearly double the risk of intraoperative anesthesia-1 in 7,138 [ 119 ]. Furthermore, some studies in rodents and primates suggest behavioral and learning disorders after administration of anesthesia, but this does not necessarily apply to humans.…”
Section: Risks Of Non-radiation-based Imaging Techniquesmentioning
confidence: 94%
“…Careful preparation in magnetically active environments seems to be more vital than in radioactive fields. While no accidental deaths were reported from the multiple center survey [10], there is one report stating that the mortality risk doubled when general anesthesia was performed in an MRI suite [29]. As the MRI-compatible precise ECG monitor is still unavailable, it has been truly difficult to set everything up like the OR.…”
Section: Discussionmentioning
confidence: 99%